Workers Rights’ Implications Who Have Experienced Termination of Employment According to The Law Number 13 of 2003 Concerning Employment - Asuan Asuan; Rizayusmanda Rizayusmanda (International Journal of Social Service and Research (IJSSR), 2023)
This journal entitled Implications of the Rights of Workers Who Experiencing Termination of Employment (PHK) According to Law Number 13 of 2003 concerning Manpower discusses legal remedies that can be taken by workers who experience Termination of Employment (PHK) as a result of not fulfilling their rights by employers and legal sanctions against employers who violate workers' rights based on Law Number 13 of 2003 concerning Manpower. The results of this study indicate that workers can submit legal remedies to employers not giving rights due to layoffs mentioned in Article 171 of Law no. 13 of 2003 concerning Manpower, namely workers/laborers who experience termination of employment without the establishment of an industrial relations dispute resolution institution and administrative (bipartid)/civil measures and legal sanctions against employers who violate workers' rights as a result of layoffs, namely criminal and administrative sanctions. Article 189 Criminal sanctions of imprisonment, confinement and/or fines do not eliminate the obligation of employers to pay rights and/or compensation to workers or workers/laborers and Article 190 paragraph (2) namely administrative sanctions, namely warnings, written warnings, restrictions on activities business, freezing of business activities, cancellation of approval, cancellation of registration, temporary suspension of part or all of the means of production, up to revocation of permits.